MODERN TECHNOLOGIES AS A BASIS FOR PREVENTING DOMESTIC VIOLENCE - Dimovski, Darko T (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Regardless of the fact that there is an appropriate normative framework for sanctioning the commission of the criminal offense of domestic violence, in practice there are numerous problems for proving it before the competent court. Therefore, the author, citing examples from practice, identified problems in proving domestic violence. At the end of the paper, the author will, listing the existing mobile applications and their shortcomings, present ways to overcome these problems by using a newly created application that will have a dual function - prevention of domestic violence and its easier proof.
Keywords: domestic violence; proving; prevention; modern technologies